1996
DOI: 10.1046/j.1365-2362.1996.133284.x
|View full text |Cite
|
Sign up to set email alerts
|

Echo‐Doppler left ventricular filling abnormalities in patients with rheumatoid arthritis without clinically evident cardiovascular disease

Abstract: Abstract. Our investigation aimed at verifying diastolic abnormalities in rheumatoid patients, without clinically evident cardiovascular disease and other confounding complaints, by using pulsed Doppler examination of transmitral blood flow. We selected 40 patients fulfilling revised American Rheumatism Association (ARA) criteria for the diagnosis of rheumatoid arthritis having no symptoms of cardiac disease or clinical findings of other extracardiac diseases. We also studied 40 rheumatoidmatched healthy volun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
0
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(31 citation statements)
references
References 23 publications
5
24
0
2
Order By: Relevance
“…To date, three systematic reviews and meta-analyses are available as cornerstones regarding cardiac alterations in RA patients [4,5,20,21]. The data of our previous meta-analysis highlights that RA patients without confounding comorbidities have first, a significant valvular, aortic root and pericardial involvement.…”
Section: Discussionmentioning
confidence: 89%
“…To date, three systematic reviews and meta-analyses are available as cornerstones regarding cardiac alterations in RA patients [4,5,20,21]. The data of our previous meta-analysis highlights that RA patients without confounding comorbidities have first, a significant valvular, aortic root and pericardial involvement.…”
Section: Discussionmentioning
confidence: 89%
“…In contrast, 4 other case-control studies reported similar LV ejection fractions in RA patients and controls but higher rates of impaired diastolic relaxation based on reductions in transmitral ratios of early to late ventricular filling (E/A ratios) in RA. [37][38][39][40][41] Similar to evidence in atherosclerosis, anti-TNF therapy may protect RA patients from developing heart failure. 34 …”
Section: Myocardial Diseasementioning
confidence: 99%
“…Heart failure may be one of the main causes of increased cardiovascular mortality in RA, particularly in men 1 . Diastolic LV dysfunction on Echo-Doppler, found in 30-40% of RA patients without overt heart disease 16 , is thought to be an early sign of IHD or heart failure and has adverse prognostic significance. Restriction due to amyloid can lead to diastolic heart failure; in the past it was found in 10-20% of rheumatoid hearts, but is now rare.…”
Section: Myocardial Dysfunctionmentioning
confidence: 99%
“…ECG and chest X-ray are useful, but are insensitive and non-specific first-line investigations. Echocardiography allows evaluation of both cardiac anatomy and function, and may be helpful in several situations 8,9,16 : pericarditis (fluid and thickening) imminent tamponade (diastolic collapse) constriction (preserved LV function but abrupt termination of ventricular filling) valvular lesions (grading of regurgitation and serial assessment of LV end-diastolic dimension) amyloidosis assessment of LV systolic and diastolic function. In cases of constriction, computed tomography (CT) scanning is useful to confirm pericardial thickening, and helps to differentiate constrictive pericarditis from restrictive cardiomyopathy ( Table 2).…”
Section: Investigation Of Cardiovascular Involvement In Rheumatoid Armentioning
confidence: 99%